PROFESIONALISME WARTAWAN DALAM PELIPUTAN BERITA RADIO DI RRI PEKANBARU - Ristiani, Ristin; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Radio Republic Indonesia (RRI) is a mass media Pekanbaru government formed in 1958 and is a subsidiary of RRI Center. Pekanbaru RRI reporters demanded to cover the news according to the schedule that has been set and any place that has been coordinated in order to meet the demands of the news coverage of the desired entire Pro can be met. Thus, this study aims to determine how the professionalism of journalists in the coverage of News Radio RRI Pekanbaru and to know the constraints of journalists in radio news coverage in RRI Pekanbaru.This study uses descriptive qualitative method. The object of this research is the Institute RRI Pekanbaru. Subjects in this study by researchers determined by statute (purposive sampling) such as Editor, Coordinator of coverage, as well as the journalists who run news coverage. Techniques used in data collection are observation informant interviews or ask the reporter RRI to obtain information and documentation that is data derived from company documentation, photo documentation researchers get on the field as the additional documentation.Based on the research found that the First, professionalism of journalists working in Pekanbaru RRI seen from the background of news coverage, any news items are loaded and educational background. Second, researchers found several obstacles journalists, namely, network technical constraints, time constraints, inadequate number of journalists or Human Resources (HR), the reporter is not of journalism education.